A simple command to calculate travel distance and travel time - Sylvain Weber; Martin Péclat (University of Neuchâtel, Institute of Economic Research (IRENE), 2017)
Obtaining the routing distance between two addresses should not be a hassle in the current state of technology. This is unfortunately more complicated than it first seems. Recently, several Stata commands have been implemented for this purpose (traveltime, traveltime3, mqtime, osrmtime), but most of them went out of order only a few months after their introduction or appear as complicated to use. In this paper, we introduce the new command georoute to retrieve travel distance and travel time between two points, defined either by their addresses or by their geographical coordinates. Compared to other existing commands, we argue it is simple to use, efficient in terms of computational speed, and versatile regarding the information that can be provided as input.
Keywords: C87; R41; 330; Stata; geocoding; travel distance; travel time